Evaluation of the clinical and laboratory characteristics of children diagnosed with celiac disease Celiac disease in children - Deveci, Ugur; Acar, Ufuk (Bayrakol Medical Publisher, 2021)
Aim: Celiac disease is an important autoimmune disease, which leads to malabsorption in childhood. Morbidity and mortality can be prevented with early diagnosis and treatment. The aim of this study was to evaluate the clinical and laboratory characteristics of children diagnosed with celiac disease. Material and Method: A retrospective evaluation was made of the medical records of patients diagnosed with celiac disease in the Paediatric Gastroenterology Department of Sanliurfa Training and Research Hospital between June 2016 and May 2018. The patients were evaluated in respect of age, gender, height, weight, complaints, age at diagnosis, and laboratory and histopathological findings. Results: A total of 201 cases were included in the study, comprising 89 (44.3%) males and 112 (55.7%) females with a mean age of 8.22 +/- 4.11 years. At the time of presentation, the primary complaints were retarded development in 96.5%, chronic diarrhea in 17.4%, constipation in 15.9%, abdominal pain in 12.4%, vomiting in 5.5%, nausea in 3.5%, and bleeding in 0.5%. Six patients had a family history of celiac disease. Iron deficiency anemia was present in 58 cases. In the pathology examination of biopsies taken from the patients, Helicobacter pylori positivity was determined in 116 (57.7%). Discussion: The clinical findings of celiac disease vary widely. In addition to gastrointestinal system findings, the most common complaint on presentation was retarded development These patients should be evaluated in respect of comorbid diseases. Following diagnosis, the necessary medical and social support should be provided for both the patient and their family.
Keywords: Celiac Disease; Malabsorption; Child